1998
DOI: 10.1300/j018v18n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prediction of Depression in American Indian Elderly

Abstract: Depression research is sparse with older AmericanIndians, and almost non-existent with Great Lakes American Indians. In our study, 309 Great Lakes American Indian elderly from urban, rural, and reservation settings were interviewed. Two-thirds of the sample were over age 65. Fifty-four percent of the sample completed less than a high school education, and 23 percent completed only a high school education. Depression prevalence and its correlates were examined. The CES-D was used to measure depressive symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…However, in a national study of 18,078 AI/AN older adults (aged 55 and above), only 13.8% of AI/ANs reported depression (Baker-Demmaray, 2012). In a study of 309 AI/AN elders, approximately 18% had significant levels of depression, which was commensurate with rates among the general population (Curyto et al, 1998). More research is needed to establish accurate prevalence rates.…”
Section: Depression Among Ai/an Older Adultsmentioning
confidence: 90%
See 4 more Smart Citations
“…However, in a national study of 18,078 AI/AN older adults (aged 55 and above), only 13.8% of AI/ANs reported depression (Baker-Demmaray, 2012). In a study of 309 AI/AN elders, approximately 18% had significant levels of depression, which was commensurate with rates among the general population (Curyto et al, 1998). More research is needed to establish accurate prevalence rates.…”
Section: Depression Among Ai/an Older Adultsmentioning
confidence: 90%
“…Research on risk and protective factors related to depression among AI/AN is scarce; research on AI/AN depression among older adults is virtually non-existent (Baker-Demmaray, 2012;Chapleski et al, 2004;Curyto et al, 1998;Miller-Cribbs et al, 2009;O'Nell, 1996). One study examined with AI/AN elders found that living in urban areas and educational level were significant predictors of depression (Curyto et al, 1998).…”
Section: Risk and Protective Factors For Depressionmentioning
confidence: 99%
See 3 more Smart Citations